Strategi Komunikasi Krisis di Era Digital pada Direktorat Jenderal Pajak Kementerian Keuangan RI - Tsabdany Tzarauliarany Anagusti; Fitria Ayuningtyas; Anter Venus (Jurnal Riset Komunikasi (JURKOM), 2024)
The phenomenon of corruption at the Directorate General of Taxes, Ministry of Finance of the Republic of Indonesia is currently in the public spotlight. This study underlines the need of responding quickly to institutional crises through the implementation of digital communication tactics. Failure to respond quickly can make an institution vulnerable to unmanageable attacks. The community aspires to be able to communicate and participate directly in overcoming the situation. As a result, institutions must move from a one-way communication strategy to a two-way interaction model via their official social media channels. A crisis can have a significant impact on public safety, financial losses, reputational harm, and other difficult-to-predict issues, therefore a crisis communication strategy is essential. This research aims to determine DJP's crisis communication strategy. This research uses a case study qualitative method approach at the DJP to obtain accurate information on crisis response. The results of the research show that the agency has had a good crisis management plan and handling since before the crisis occurred; the crisis response and after the crisis have continuously been monitored regularly in various media, from content creation on social media, information on the official website to establishing good relations. with various media both nationally and internationally. DJP is also collaborating with Public Relations service centers in all regional offices and employee advocacy through the institution's official social media account to open as many communication channels as possible so that the public can well receive the message. Statements and firm steps were then disseminated through DJP's social media platforms and official websites to resolve the crisis.